Medicinal mushrooms: Towards a new horizon - Ganeshpurkar, A.; Rai, G.; Jain, A. P. (Pharmacognosy Reviews)
The arising awareness about functional food has created a boom in this new millennium. Mushrooms are widely consumed by the people due to their nutritive and medicinal properties. Belonging to taxonomic category of basidiomycetes or ascomycetes, these mushrooms possess antioxidant and antimicrobial properties. They are also one of the richest source of anticancer and immunomodulating agents. Thus these novel myochemicals from these mushrooms are the wave of future.
Keywords: Anticancer; antimicrobials; antioxidants; immunomodulators; mushrooms; myochemicals